Peningkatan Keterampilan Pengukuran Antropometri pada Kader Posyandu Sebagai Upaya Pencegahan Stunting - Raudhatul Munawarah; Endah Dian Marlina; Rosita Syaripah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Background: Stunting in toddlers can have an impact on children's health and intelligence in the future, such as the body's resistance to infections or viruses and decreased academic performance. Objective: to train posyandu cadres in improving anthropometric measurement skills in toddlers. Method: The method used in this activity is providing materials, training and simulation of anthropometric measurements. The targets for this activity are posyandu cadres from RW 03, Pulo Gebang Village. This community service activity will be carried out in August 2024 at the RW 03 hall, Pulo Gebang Village. Results: the implementation of this community service resulted in an increase in posyandu cadres' understanding of stunting and anthropometric measurement methods with good understanding from 2% to 76%. Cadres with sufficient understanding are 24%. Conclusion: Improving the skills of posyandu and KIE cadres regarding stunting can improve stunting prevention efforts.